The BIS and hemodynamic changes in major burn patients according to a slow infusion of propofol for induction - Ji Young Bae; Do Young Choi; Chul-Ho Woo; In-Suk Kwak; Sung Ha Mun; Kwang-Min Kim (Korean Journal of Anesthesiology, 2011)
BackgroundMany pathophysiologic alterations in patients with major burns can cause changes in the response of propofol. The aim of this study is to determine the appropriate induction dose of propofol using a slow infusion rate for major burn patients to obtain desirable sedation and hypnotic conditions with minimal hemodynamic changes.Methods45 adults with major burns and who were electively scheduled for escharectomy less than a week after injury were recruited. For induction with propofol, the patients were randomly allocated to one of two groups (group 1: 1.5 mg/kg, n = 20 and group 2: 2.0 mg/kg, n = 25). The infusion rate was 20 mg/kg/hr. The systolic and diastolic blood pressure (SBP, DBP), the heart rate, the bispectral index and the modified observers' assessment of the alertness/sedation scale (OAA/S) were measured before the induction and after the propofol infusion, as well as immediately, 3 and 5 minutes after intubation.ResultsThe SBP and DBP were significantly decreased after the propofol infusion in both group, but there were no significant differences between the two groups. The BIS values after the propofol infusion and intubation were 44.2 ± 16.1 and 43.5 ± 13.8 in group 1, and 45.6 ± 10.3 and 46.5 ± 11.4 in group 2, respectively, and there were no differences between the 2 groups.ConclusionsWhen propofol is administrated to major burn patients, an induction dose of 1.5 mg/kg is appropriate and a slow infusion rate of 20 mg/kg/hr is safe for maintaining the desired hypnotic conditions and this dose and rate cause no significant hemodynamic problems.